2020
DOI: 10.3389/fmicb.2020.01335
|View full text |Cite
|
Sign up to set email alerts
|

Breast-Milk Microbiota Linked to Celiac Disease Development in Children: A Pilot Study From the PreventCD Cohort

Abstract: Celiac disease (CeD) is an immune-mediated disorder triggered by exposure to dietary gluten proteins in genetically predisposed individuals. In addition to the host genome, the microbiome has recently been linked to CeD risk and pathogenesis. To progress in our understanding of the role of breast milk microbiota profiles in CeD, we have analyzed samples from a subset of mothers (n = 49) included in the PreventCD project, whose children did or did not develop CeD. The results of the microbiota data analysis ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 63 publications
(72 reference statements)
0
13
1
Order By: Relevance
“…Given that the majority of available microbiome and virome literature at this time is at the species level, here we focus the discussion of our results at the species level. While a previous study which utilized 16S sequencing did not identify differences in the breast milk microbiota of subjects with CD compared with healthy controls [ 27 ], we identified statistically significant differences in eight bacterial species and two viral species between the two groups. The eight bacteria isolated in our study have previously been isolated from the breast milk of healthy subjects [ 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ].…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…Given that the majority of available microbiome and virome literature at this time is at the species level, here we focus the discussion of our results at the species level. While a previous study which utilized 16S sequencing did not identify differences in the breast milk microbiota of subjects with CD compared with healthy controls [ 27 ], we identified statistically significant differences in eight bacterial species and two viral species between the two groups. The eight bacteria isolated in our study have previously been isolated from the breast milk of healthy subjects [ 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ].…”
Section: Discussioncontrasting
confidence: 74%
“…One case-control study utilized polymerase chain reaction (PCR)-based techniques and found a reduced abundance of Bifidobacterium species in mothers with CD when compared with mothers without CD at one month after delivery [ 26 ]. Another study compared the breast milk microbiota of subject’s whose children later did or did not develop CD at 9 months after delivery using 16S rRNA sequencing [ 27 ]. While they did not identify significant differences between the breast milk microbial composition in subjects with or without CD, they found that the breast milk of subjects whose children later developed CD had an increased abundance of Methylobacterium komagatae, Methylocapsa palsarum , and Bacteroides vulgatus [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…The multiple sequence alignment from the 80 amino acid C-terminus of CcrM (Figure 7 ) reveals conservation among a variety of N4/N6-DNA methyltransferases from alphaproteobacteria. The organisms listed represent this variety and include human pathogens Rhodobacter massiliensis ( 46 ), Pannonibacter pragmitetus ( 47 ), Inquilinus limosus ( 48 ), Haematospirillum jordaniae ( 49 ) and Methylocapsa palsarum ( 50 ), a bacteria that contributes to biogas production Rhodopseudomonas faecalis ( 51 ), a plant-growth promoting bacteria Azospirillum sp. RU38E ( 52 ), two methanotrophs Methylocapsa palsarum ( 53 ) and Methylocella silvestris ( 54 ), and Tepidicaulis Marinus , which reduces nitrate ( 55 ).…”
Section: Resultsmentioning
confidence: 99%
“…In the breast milk of mothers with celiac disease, the levels of cytokines, Bacteroides spp., and Bifidobacterium spp. were reduced [128]. Women diagnosed as HIV-positive had higher bacterial diversity and higher prevalence of Lactobacillus spp.…”
Section: Maternal Health Statusmentioning
confidence: 99%